ScCO2-driven multiscale porosity evolution in coal: Mineral-coupled reconstruction mechanisms and CO2-ECBM implications - Hengyi He; Peng Liu; Baisheng Nie; Xiao Cui; Jingtao Yang; Hao Zhang; Wanjun Chen; Song Bao (Fuel, 2026)

Microbial drivers of enhanced nitrogen use efficiency and concurrent N2O emissions in a garlic–rice rotation system - Yanqiu Chen; Zhitao Hu; Chengyang Ji; Wenwen Song; Xin Ni; Chunlian Jin; Yong Chen; Fei Deng; Xiaolong Lei; Youfeng Tao; Hong Cheng; Wanjun Ren; et al. (Applied Soil Ecology, 2026)

Effects of ABC transporter polymorphism on the pharmacokinetics of pentoxifylline and its active metabolites in healthy Chinese subjects - Lingfang Guo; Xue Sun; Bo Qiu; Wanjun Bai; Yabin Du; Haojing Song (European Journal of Clinical Pharmacology, 2026)

Greenhouse gas emissions during the rice season are reduced by a low soil C:N ratio using different upland-paddy rotation systems - Tao Wang; Chengyang Ji; Wei Zhou; Hong Chen; Yong Chen; Qi Liu; Tao Cao; Chunlian Jin; Wenwen Song; Fei Deng; Xiaolong Lei; Youfeng Tao; et al. (Field Crops Research, 2024)

Realization of skyrmion shift register - Le Zhao; Chensong Hua; Chengkun Song; Weichao Yu; Wanjun Jiang (Science Bulletin, 2024)

Mutation of a highly conserved amino acid in RPM1 causes leaf yellowing and premature senescence in wheat - Wenjia Zhang; Zhaoheng Zhang; Qian Chen; Zihao Wang; Wanjun Song; Kai Yang; Mingming Xin; Zhaorong Hu; Jie Liu; Huiru Peng; Jinsheng Lai; Weilong Guo; et al. (Theoretical and Applied Genetics, 2023)

An anisotropic electromagnetic hydrogel promotes cardiomyocyte maturation and post-infarction cardiac repair - Xiaopei Li; Peng Lu; Zhaoyang Liu; Ziang Wen; Xiangyu Li; Chufan Wang; Wanjun Jin; Bin Zhou; Ningping Huang; Meijuan Song; Xiaowei Wang (Chemical Engineering Journal, 2023)

The Essential Role of W5 in Wax Metabolism in Wheat (Triticum aestivum L.) - Linghong Li; Zhe Zhang; Wanjun Song; Zhenqi Su; Yufeng Zhang; Mingshan You; Zhongfu Ni; Jiewen Xing (Journal of Plant Biology, 2022)

Groundwater quality assessment and hydrogeochemical processes in typical watersheds in Zhangjiakou region, northern China - Wanjun Jiang; Yizhi Sheng; Hongwei Liu; Zhen Ma; Yaxin Song; Futian Liu; Sheming Chen (Environmental Science and Pollution Research, 2022)

The decreased expression of GW2 homologous genes contributed to the increased grain width and thousand‑grain weight in wheat-Dasypyrum villosum 6VS·6DL translocation lines - Zhiyu Feng; Long Song; Wanjun Song; Zhongqi Qi; Jun Yuan; Run Li; Haiming Han; Huifang Wang; Zhaoyan Chen; Weilong Guo; Mingming Xin; Jie Liu; et al. (Theoretical and Applied Genetics, 2021)

Molecular characterization and phylogenetic analysis of Wx genes of four diploid species of the Triticeae genera Eremopyrum, Psathyrostachys, and Henrardia - Shoufen Dai; Junru Li; Jiangwei Huang; Zhi Zhai; Wanjun Yang; Qianyu Liu; Yuanyuan Zuo; Zhongping Song; Jian Li; Gang Liu; Guoyue Chen; Yuming Wei; et al. (Genetic Resources and Crop Evolution, 2021)

Pleiotropic function of the SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE gene TaSPL14 in wheat plant architecture - Jie Cao; Kaiye Liu; Wanjun Song; Jianing Zhang; Yingyin Yao; Mingming Xin; Zhaorong Hu; Huiru Peng; Zhongfu Ni; Qixin Sun; Jinkun Du (Planta, 2021)
Main conclusion The function of SQUAMOSA PROMOTER-BINDING PROTEIN-BOX gene TaSPL14 in wheat is similar to that of OsSPL14 in rice in regulating plant height, panicle length, spikelet number, and thousand-grain weight of wheat, but differs during tiller development. TaSPL14 may regulate spike development via ethylene-response gene EIN3-LIKE 1 ( TaEIL1 ), ETHYLENE-RESPONSIVE TRANSCRIPTION FACTOR 2.11 ( TaRAP2.11 ), and ETHYLENE-RESPONSIVE TRANSCRIPTION FACTOR 1 ( TaERF1 ), but not DENSE AND ERECT PANICLE 1 ( TaDEP1 ) in wheat. Abstract The SQUAMOSA PROMOTER-BINDING PROTEIN-LIKE gene OsSPL14 from rice is considered to be a major determinant of ideal plant architecture consisting of few unproductive tillers, more grains per spike, and high resistance of stems to lodging. However, the function of its orthologous gene, TaSPL14 , in wheat is unknown. Here, we reported the functional similarities and differences between TaSPL14 and OsSPL14 . Similar to OsSPL14 knock-outs in rice, wheat TaSPL14 knock-out plants exhibited decreased plant height, panicle length, spikelet number, and thousand-grain weight. In contrast to OsSPL14 , however, TaSPL14 did not affect tiller number. Transcriptome analysis revealed that the expression of genes related to ethylene response was significantly decreased in young spikes of TaSPL14 knock-out lines as compared with wild type. TaSPL14 directly binds to the promoters of the ethylene-response genes TaEIL1 , TaRAP2.11, and TaERF1, and promotes their expression, suggesting that TaSPL14 might regulate wheat spike development via the ethylene-response pathway. The elucidation of TaSPL14 will contribute to understanding of the molecular mechanisms that underlie wheat plant architecture.

Use of near-isogenic lines to precisely map and validate a major QTL for grain weight on chromosome 4AL in bread wheat (Triticum aestivum L.) - Panfeng Guan; Na Di; Qing Mu; Xueyi Shen; Yongfa Wang; Xiaobo Wang; Kuohai Yu; Wanjun Song; Yongming Chen; Mingming Xin; Zhaorong Hu; Weilong Guo; et al. (Theoretical and Applied Genetics, 2019)

Spatio-temporal Variation of Soil Respiration and Its Driving Factors in Semi-arid Regions of North China - Xinhua Zeng; Yigang Song; Wanjun Zhang; Shengbing He (Chinese Geographical Science, 2018)

Highly sensitive fluorescence biosensors for sparfloxacin detection at nanogram level based on electron transfer mechanism of cadmium telluride quantum dots - Wanjun Liang; Shaopu Liu; Jing Song; Chenxia Hao; Linlin Wang; Dan Li; Youqiu He (Biotechnology Letters, 2015)

MicroRNA-148a suppresses epithelial-to-mesenchymal transition by targeting ROCK1 in non-small cell lung cancer cells - Jipeng Li; Yulan Song; Yiping Wang; Jianping Luo; Wanjun Yu (Molecular and Cellular Biochemistry, 2013)